Intramyocardial choristoma-a rare entity: first-ever case report and literature review - Francis, Thomas; Kuthubuddeen, Muhammad Hilmi; Ranganathan, Radhikkhaa; Hamzah, M. K.; Arif, M. N. M.; Jasid, Abdul Muiz (International Surgery Journal, 2023)
We report the first-ever case of ‘Intramyocardial choristoma’ documented in English-language literature. A 71-year-old woman, during her preoperative echocardiogram assessment, noted to have a large left ventricle (LV) mass with severe mitral regurgitation (MR). The patient was asymptomatic, with CT scan reported a large dense calcified LV mass. She underwent mitral valve replacement with LV mass resection operation. The mass was completely excised. Histopathological examinations show intramyocardial choristoma, with the lesion shows cardiac muscle with areas of calcification and mature bone tissue, with clear margins. Discharged well post operatively. Commonest clinical scenarios for intracardiac masses are myxomas, infective endocarditis with vegetation and thrombus. Primary cardiac tumours are very rare. Choristoma are rare benign tumour, with histologically normal tissues in an abnormal location, with a very rare recurrence rate. Transthoracic echocardiogram is reliable for the evaluation of the intracardiac masses, but the use of contrast echocardiogram gives additional benefit in analysing the characteristics of the intracardiac mass. For complex lesion, such as intramural component, extension into the inflow or outflow and into pericardial/extracardiac, MRI have added benefits. The treatment of choice is complete surgical resection. Follow up surveillance scans are recommended, as there is a very low risk of recurrence with uncertain prognosis. A multidisciplinary team approach is highly recommended in managing the patient pre-operative, intra-operative and post-operatively. Post operatively, regular follow up with imaging is recommended.